Effect of Al3(Sc, Zr) and Mg2Si precipitates on microstructure and tensile properties of selective laser melted Al-14.1Mg-0.47Si-0.31Sc-0.17Zr alloy. (August 2020) - Bi, Jiang; Lei, Zhenglong; Chen, Yanbin; Chen, Xi; Tian, Ze; Qin, Xikun; Liang, Jingwei; Zhang, Xinrui
Abstract: A novel Al-14.1Mg-0.47Si-0.31Sc-0.17Zr alloy with a low density of 2.54 g/cm 3 and a high tensile strength of 510 MPa was manufactured using selective laser melting (SLM) at 200 W and 500 mm/s. The SLM-processed alloy has the comprehensive characteristics of the 5xxx and 6xxx series Al alloys due to its optimized composition. The formation of equiaxed grains occurred during the SLM process, and the mean grain size was 2.97 μm 2 in the as-printed (AP) condition. With a heat treatment (HT) of 325 °C for 4 h, the grain size was nearly unchanged (3.45 μm 2 ), and the tensile strength increased to 571 MPa with the formation of Al3 (Sc, Zr) and Mg2 Si nanoparticles. This new AlMgSiScZr alloy has promising prospects for replacing some specialized titanium parts in the future. Graphical abstract: Image 1 Highlights: A novel AlMgSiScZr alloy with low density and high strength was prepared by SLM. The SLM sample has comprehensive characteristics of 5xxx and 6xxx series Al alloys. This new alloy is hopeful to replace some specialized titanium parts in the future.